Farmers' participatory management of diseases for higher yield and nutritive value of crop residues of groundnut, Deccan Plateau, India. Proceedings of a workshop - International Crops Research Institute for the Semi-Arid Tropics (International Crops Research Institute for the Semi-Arid Tropics, 2006)
Groundnut (Arachis hypogaea L.) is one of the most important oilseed crops in the rainfed areas of the Deccan Plateau in India, providing nutritious fodder for ruminants. For several decades, farmers in this region have been cultivating the traditional cultivar TMV 2. However, they have been plagued by economically significant foliar diseases like late leaf spot and rust, leading to low and poor pod and fodder yields. ICRISAT (International Crops Research Institute for the Semi-Arid Tropics) for the past decade in collaboration with partner institutes has been striving to develop a new cultivar. Following several on-station and on-farm studies, a dual purpose, early maturing groundnut cultivar ICGV 91114 and its Integrated Disease Management (IDM) technology were developed as a substitute for TMV 2. The package includes the economical use of fungicide as seed treatment and foliar application. This workshop was conducted to critically review the results of the studies conducted over the last two years and ascertain how to make best use of the finding. The papers in this proceeding are divided in five sessions. The first session "Integrated crop and pest management in groundnut" discusses improved crop husbandry practices in groundnut in dryland agriculture; integrated management of fungal and other diseases & insect pests and their management. The second session "Farmers' participatory on-farm integrated disease management in groundnut" looks into the influence of IDM on groundnut yield; farmers' participatory crop and disease management; upscaling of dual purpose, short duration groundnut genotype; and crop management practices. The third session "Diseased haulum, yield, nutrition and digestibility" examines the effect of diseased groundnut and sorghum crop residues on nutrient utilization in cattle; stover quality of crop residues; and feeding diseased vs healthy haulums. In this session is also presented the finding from on-farm participatory rural appraisals - the ILRI experience. Session four "Harvest management and marketing of pod and fodder (haulums) in groundnut" discusses management of harvesting in groundnut; the present marketing system for groundnuts; and marketing groundnut pods and fodder. Topics of discussion in the session "Linkages and seed systems" includes sorghum for mixed crop-livestock systems; seeds of choice for sustainable agriculture; village level seed system in groundnut; and the existing seed system at the village level.